Circatrigintan instead of lunar periodicity of larval release in a brooding coral species - Bart Linden (Nature Portfolio, 2018)
Abstract Larval release by brooding corals is often assumed to display lunar periodicity. Here, we show that larval release of individual Stylophora pistillata colonies does not comply with the assumed tight entrainment by the lunar cycle, and can better be classified as a circatrigintan pattern. The colonies exhibited three distinct reproductive patterns, characterized by short intervals, long intervals and no periodicity between reproductive peaks, respectively. Cross correlation between the lunar cycle and larval release of the periodic colonies revealed an approximately 30-day periodicity with a variable lag of 5 to 10 days after full moon. The observed variability indicates that the lunar cycle does not provide a strict zeitgeber. Other factors such as water temperature and solar radiation did not correlate significantly with the larval release. The circatrigintan patterns displayed by S. pistillata supports the plasticity of corals and sheds new light on discussions on the fecundity of brooding coral species.